Potential of flavor enhancer from crude hydrolysate derived from Pomacea canaliculata and Filopaludina javanica using papain - Yusuf Trisna Putra, Andre; Finatsiyatull Rosida, Dedin; Dany Priyanto, Anugerah; Kongpichitchoke, Teeradate; Havanapan, Phattara-Orn (Hasanuddin University Food Science and Technology Study Program, 2025)
Enzymatic hydrolysis is an effective technique for breaking down proteins into peptides and free amino acids. Among the amino acids released, glutamic acid (glutamate) plays a key role in generating the umami taste in snails. This study aimed to produce a natural flavor enhancer through the enzymatic hydrolysis of proteins derived from Pomacea canaliculata (PCP) and Filopaludina javanica (FJP) using papain enzyme. The hydrolysis process was conducted by adding papain to PCP and FJP slurries at different enzyme-to-substrate (E/S) ratios of 1:10, 1:20, and 1:100 (w/v). The reaction was carried out at 54 °C for 3, 6, 9, 12, 15, and 18 hours. After incubation, the supernatant was collected and analyzed for the degree of hydrolysis, total peptide content, total amino acids, sensory properties, and peptide sequence identification using LC-ESI-MS/MS. The highest degree of hydrolysis was obtained at an E/S ratio of 1:10 after 18 hours, yielding 89.28% for PCP and 76.27% for FJP. The highest peptide concentrations were 15.28 mg/mL and 8.60 mg/mL for PCP and FJP hydrolysates, respectively. Increasing enzyme concentration positively influenced panelists’ preferences for taste, color, and aroma attributes. The identified umami peptides from PCP and FJP typically contained 8–39 amino acids. In the PCP hydrolysate, Ala and Gly residues were identified at the N-terminal region of several peptides, including AVGLSHSNNTKDVMEKSK, GFMCSVDDQHTSSVLLLSYNAITGLGFTTCVTMIA, and GEMAAHYGTMDGGPGM. In the FJP hydrolysate, Gly was predominantly present at the N-terminal of peptides such as GLPGLPGLPGPK, GPLGPLGPQGIP, and GMMPPGMMPPEGMPP